2021
DOI: 10.48550/arxiv.2105.13721
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chiral superconductivity in UTe2 probed by anisotropic low-energy excitations

Abstract: Chiral spin-triplet superconductivity is a topologically nontrivial pairing state with broken time-reversal symmetry, which can host Majorana quasiparticles [1,2]. The recently discovered heavy-fermion superconductor UTe 2 [3] exhibits peculiar properties of spin-triplet pairing [3][4][5][6], and the possible chiral state has been actively discussed [7][8][9]. However, the symmetry and nodal structure of its order parameter in the bulk, which determine the Majorana surface states [2],remains controversial [10]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 27 publications
2
23
0
Order By: Relevance
“…Polar Kerr effect measurements combined with theoretical modelling revealed that the superconducting order parameter breaks time-reversal symmetry and is likely to contain Weyl nodes 5 . More recently, magnetic penetration depth measurements revealed temperature scaling consistent with a multi-component spin-triplet state 6 . UTe 2 also exhibits striking phase diagrams as a function of applied pressure and magnetic fields.…”
mentioning
confidence: 95%
“…Polar Kerr effect measurements combined with theoretical modelling revealed that the superconducting order parameter breaks time-reversal symmetry and is likely to contain Weyl nodes 5 . More recently, magnetic penetration depth measurements revealed temperature scaling consistent with a multi-component spin-triplet state 6 . UTe 2 also exhibits striking phase diagrams as a function of applied pressure and magnetic fields.…”
mentioning
confidence: 95%
“…These findings suggest that UTe 2 is a potential candidate for odd-parity SCs. In addition, recent experimental studies have reported unconventional superconducting properties [24] such as the existence of point nodes [25,26], time-reversal symmetry breaking [27][28][29], and nonunitary pairing involving multiple components [28,30,31]. Thus, UTe 2 is a promising platform for studying nonunitary odd-parity SCs with point nodes.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In particular, we found that the point nodes of types (i) and (iv) can be distinguished from others by observing the temperature dependence of (1/T 1 ) /(1/T 1 ) ⊥ , where the subscripts and ⊥ denote the values at θ I = 0 and π/2, respectively. Finally, we discuss the implications of our results for the recently discovered superconductivity in UTe 2 [23] which is a promising material candidate for a nonunitary odd-parity SC with point nodes [24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the quasiparticle current, Eqs. ( 51) and (52) show that the clapping modes (δE ± ) carry the electric current. In particular, the clapping modes (δE ± ) lead to a transverse electric current, flowing perpendicular to the direction of propagation of the acoustic wave.…”
Section: Anomalous Acoustoelectric Effect Induced By Clapping Modesmentioning
confidence: 98%
“…The angleresolved NMR measurements in UCoGe suggest non-unitary chiral order with the d-vector represented by d(k) ∼ (a 1 k a + ia 2 k b , a 3 k b + ia 4 k a , 0), where a i (i = 1, 2, 3, 4) are real coefficients [48,49]. Recently, non-unitary chiral superconductivity was also proposed in UTe 2 , where the normal state is paramagnetic, but superconductivity survives even at extremely high magnetic fields over 40 T [50][51][52][53]. The superconducting state from the paramagnetic normal state shares many common features with ferromagnetic superconductors, including strong magnetic Ising anisotropy and the reentrant superconducting transition [54,55].…”
mentioning
confidence: 99%